Gamification Design of Computer Network Virtual Laboratory Using SAGD-VL Framework - Sany, Diny Syarifah (POLITEKNIK NEGERI JAKARTA, 2023)
Building gamification in a virtual laboratory of the computer network will help students to be able to do practicums anywhere and be able to meet the needs of practicum tools and materials. However, researchers have not found a gamification design in a virtual laboratory of the computer network laboratory that can assist developers in building virtual laboratory gamification. Based on these problems, the researcher proposes a gamification design for a virtual laboratory of the computer network using components from the SAGD-VL framework. The SAGD-VL framework is a framework for building games in virtual laboratories. This study does not take all the elements of SAGD-VL but adjusts the results of the analysis from data collection. Technology analysis aims to produce fast and true-to-life virtual laboratory gamification technology designs. This study implements the proposed design in a virtual computer network laboratory to test the proposed design. This study tested the black box, pre-test, and post-test. This test resulted in an average increase in student scores of 32.353 with the highest increase of 60. So that the proposed design of a computer network virtual laboratory gamification using SAGD-VL can help improve students' understanding of practical learning. The questionnaire results in this application being fast in computation and the UI/UX of this application is like the original.